Distinguishing commercially grown Ganoderma lucidum from Ganoderma lingzhi from Europe and East Asia on the basis of morphology, molecular phylogeny, and triterpenic acid profiles. (July 2016) - Hennicke, Florian; Cheikh-Ali, Zakaria; Liebisch, Tim; Maciá-Vicente, Jose G.; Bode, Helge B.; Piepenbring, Meike
Graphical abstract: Two commercial strains of Ling-zhi or Reishi mushrooms sold as Ganoderma lucidum are distinguished and identified as G. lucidum and G. lingzhi on the basis of their morphology, molecular phylogeny, and triterpenic acid profiles. Highlights: A triterpenic acid profile of Ganoderma lucidum s.str. is shown for the first time. G. lucidum (M9720) contained markedly less triterpenic acids than G. lingzhi (M9724). HPLC profiles show species specific tendencies probably useful for chemotaxonomy. Characteristics to distinguish G. lingzhi (M9724) from G. lucidum (M9720) are shown. This case study underlines the importance of taxonomy for commercial use of fungi. Abstract: In China and other countries of East Asia, so-called Ling-zhi or Reishi mushrooms are used in traditional medicine since several centuries. Although the common practice to apply the originally European name ' Ganoderma lucidum ' to these fungi has been questioned by several taxonomists, this is still generally done in recent publications and with commercially cultivated strains. In the present study, two commercially sold strains of ' G. lucidum ', M9720 and M9724 from the company Mycelia bvba (Belgium), are compared for their fruiting body (basidiocarp) morphology combined with molecular phylogenetic analyses, and for their secondary metabolite profile employing an ultra-performance liquid chromatography–electrospray ionization mass spectrometry (UPLC–ESIMS) in combination with a high resolution electrospray ionization mass spectrometry (HR-ESI-MS). According to basidiocarp morphology, the strain M9720 was identified as G. lucidum s.str. whereas M9724 was determined as Ganoderma lingzhi . In molecular phylogenetic analyses, the M9720 ITS and beta-tubulin sequences grouped with sequences of G. lucidum s.str. from Europe whereas those from M9724 clustered with sequences of G. lingzhi from East Asia. We show that an ethanol extract of ground basidiocarps from G. lucidum (M9720) contains much less triterpenic acids than found in the extract of G. lingzhi (M9724). The high amount of triterpenic acids accounts for the bitter taste of the basidiocarps of G. lingzhi (M9724) and of its ethanol extract. Apparently, triterpenic acids of G. lucidum s.str. are analyzed here for the first time. These results demonstrate the importance of taxonomy for commercial use of fungi.